Hydrologic modelling for green roof systems - Law, Kar Mun (2014)
Rapid development and increasing population has posed urban storm water management issues to the society. Green roof system is introduced to modern development as a method to mitigate these issues. The focus of this project is to come out with a reliable modelling system for green roof. An experimental green roof is set up on the rooftop of School of Civil and Environmental Engineering at Nanyang Technological University, consisting of two green roof units and one control brick roof unit. Several parameters such as rainfall depth and temperature are monitored. The data collected from September to and December 2012 is used to evaluate the performance of green roof compared to control brick roof. To simplify the evaluation process, only data from one of the green roof units is used. Runoff data from both the green roof and control roof is used to generate hydrographs for comparisons. Comparisons of green roof hydrological performance under different rainfall conditions are conducted to have a better understanding of relationship between green roof hydrological performance and rainfall. In addition, the performance of green roof units is compared with the performance of control brick roof in order to come out with a more complete and comprehensive conclusion. Despite of the green roof has its maximum capacity, the results show that green roof has a better performance in term of storm water runoff delay and peak flow rate reduction compared to control brick roof. The green roof is able to delay runoff as long as 51 minutes and reduce runoff flow rate as much as 1.16715E-05 m3/s depending on rainfall conditions. In low intensity and short duration rainfall events, performance of green roof in term of runoff delay and peak flow rate reduction is much better than conventional brick roof.